THE CARS WITH PETROL ENGINES AND EUROPEAN EMISSION STANDARDS - Kovac, Bronislav; Dudacek, Jiri; Surovec, Pavel (Doprava a spoje, 2006)
The paper analyses a development of European Threshold Limits from Euro 1 to Euro 5 for passenger cars (category M1) with petrol engines and On Board Diagnostic. New requirements on engine construction and emission regulation in exhaust fumes are expected from starting Euro 5 stage since 2008. In conclusion the paper informs about the latest knowledge of fuel injection, engine construction set-up, optimisation of three way catalytic converter, installation of On Board Diagnostic (OBD), fuel consumption reduction using of Multi Point Injection and minimisation of oil consumption. Realising the requirements is a premise to accomplish European Threshold Limits Euro 4 and Euro 5.